2019
DOI: 10.2147/ott.s186365
|View full text |Cite
|
Sign up to set email alerts
|

<p>INPP4B promotes colorectal cancer cell proliferation by activating mTORC1 signaling and cap-dependent translation</p>

Abstract: Background and objective Inositol polyphosphate 4-phosphatase type II (INPP4B) is over-expressed in CRC tissues, and emerges as an oncogene. However, the mechanism by which INPP4B regulates CRC cell proliferation remains largely unclear. In this study, we aimed to investigate the regulatory mechanisms of INPP4B in CRC. Materials and methods The expression levels of mRNA were detected by qRT-PCR. The expression levels of protein were determined by Western blot. Cell Coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It acts as a phosphoinositide phosphatase that is required for the engagement and recruitment of PI3K through the activation of AKT or SGK3. INPP4B may have a dual oncogenic/tumor suppressor role and was found as an oncogenic regulator in colon cancer, acute myeloid leukemia and in a subset of melanomas [21,22]. The confirmation of higher INPP4B expression in Group 1 tumors by traditional immunohistochemistry adds to the validity of DSP methods as a useful screening tool for biomarkers of interest in RMS [23].…”
Section: Discussionmentioning
confidence: 84%
“…It acts as a phosphoinositide phosphatase that is required for the engagement and recruitment of PI3K through the activation of AKT or SGK3. INPP4B may have a dual oncogenic/tumor suppressor role and was found as an oncogenic regulator in colon cancer, acute myeloid leukemia and in a subset of melanomas [21,22]. The confirmation of higher INPP4B expression in Group 1 tumors by traditional immunohistochemistry adds to the validity of DSP methods as a useful screening tool for biomarkers of interest in RMS [23].…”
Section: Discussionmentioning
confidence: 84%
“…Previous results also indicate that INPP4B overexpression in colon cancer activates AKT[ 18 , 19 ]. A similar phenomenon in which INPP4B overexpression leads to increased AKT expression has also been found in esophageal cancer[ 20 ].…”
Section: Inpp4b and Conlon Cancermentioning
confidence: 78%
“…The study also found that the activation of AKT and SGK3 was blocked by silencing INPP4B ( P < 0.05), thereby inhibiting the proliferation of colon cancer cells and delaying the growth of xenograft tumors of colon cancer. Ruan et al [ 19 ] found that INPP4B promoted colorectal cancer by activating the mTORC1 signaling pathway and cap-dependent cAMP-activated protein ( P < 0.05). This process was also found to be associated with increased AKT and SGK3 expression ( P < 0.05).…”
Section: Inpp4b and Conlon Cancermentioning
confidence: 99%
“…mTOR (comprising two main complexes, mTORC1 and mTORC2) exhibits a complicated dynamic behavior to influence the fate of cancer cells. [28][29][30] The mTORC1 branch is the central driver of cell progression via protein modulation, lipid synthesis, and energy metabolism in mammals, and is found to be deregulated in various malignancies. After the activation of mTORC1, the phosphorylation and activation of a key downstream effector, namely ribosomal protein S6 kinase (S6K), was also observed.…”
Section: Discussionmentioning
confidence: 99%